Financial Development and Innovation Dynamics - Veselinović, Nevena; Radonjić, Ljubivoje (Anali Ekonomskog fakulteta u Subotici, 2025)
The study examines the relationship between financial development and innovation in Western Balkan and Central and Eastern European countries. Empirical analysis based on panel data confirms that both banking-oriented and market-oriented financial development significantly enhance national innovation capacity. The application of the Feasible Generalized Least Squares method ensures statistical robustness by addressing heteroskedasticity, autocorrelation, and cross-sectional dependence. The findings emphasize the importance of a balanced financial system, where integrating banking and capital markets improves capital allocation and risk management, fostering long-term innovation sustainability. This study contributes to the literature by providing empirical evidence on the dual role of financial development in transition economies. The results have practical implications for policymakers, suggesting that strengthening both segments of the financial system can create a more dynamic environment for innovation and economic competitiveness. The study is limited to a specific group of countries and does not account for potential variations in financial structures, leaving space for future research to expand the sample, apply dynamic models, and explore the qualitative impact of financial policies on innovation.